Sexual Function of Women with and without Pregnancy-Related Pelvic Girdle Pain and its Relationship with Physical Activity, Kinesiophobia and Body Image: A Cross-Sectional Comparative Study - Yenisehir, Semiha; Karakaya, Ilkim Citak; Ozbey, Gurkan (Springer Heidelberg, 2024)
The aim of this study was to compare the sexual function of women with and without pregnancy-related PGP, and to investigate its relationship with physical activity (PA), kinesiophobia, and body image (BI). Demographic characteristics, sexual function (Pregnancy Sexual Response Inventory), PA (Pregnancy Physical Activity Questionnaire), kinesiophobia (Tampa Kinesiophobia Scale), and BI (Body Image in Pregnancy Scale) of 125 pregnant women were recorded. In the PGP group (n = 46), visual analogue scales were used to assess the pain intensity during resting and sexual activity, and Pelvic Girdle Questionnaire was used to evaluate the activity limitation. Although total sexual function and BI scores of the groups were similar (p > 0.05), dyspareunia during pregnancy and level of kinesiophobia were higher, and energy expenditure during moderate-intensity PA was lower in pregnant women with PGP (p < 0.05). The PGP group had moderate activity limitation and reported increased PGP intensity during sexual activities (p < 0.001). PA level was significantly correlated with sexual desire (r = 0.180), and overall sexual function was correlated with kinesiophobia (r = -0.344) and BI (r = -0.199) during pregnancy (p < 0.05). These findings suggest that pregnant women with PGP are more vulnerable to sexual dysfunctions, and there is a need to develop biopsychosocial framework-oriented management strategies which aim to improve PA level and to eliminate psychological factors such as kinesiophobia and negative BI.
Keywords: Activity limitation; Body image; Kinesiophobia; Posterior pelvic pain; Sexual dysfunction